Rancang Bangun Solar Tracker Single Axis Dengan Motor Power Window DC CSD60-B - Fakhri Al-Akhyar Putra Bumi; Erwan Eko Prasetiyo; Gaguk Marausna (Jurnal Teknologi Terpadu, 2022)
Solar power plants are one of the results of the development of energy source processing technology by utilizing solar energy converted into electrical energy using solar panels. The research objective is to obtain a conceptual design that is effective on a single axis solar tracker, so that it can absorb sunlight optimally. single axis solar tracker motor drive capable of detecting light sources. The research method using the development method (Research and Development) is a research method used to produce certain products by assessing the effectiveness of the products produced. The results of the research on single axis design using the generated DC CSD60-B power window; 3 (three) variants of the single axis solar tracker design concept, namely the horizontal axis force concept, the leg component concept, the moment force or torque concept with a capacity of 2 pv 100 wp units. Specifications for the size of the upper frame structure: length 150 -160 cm, width 100 – 110 cm and thickness 4-5 cm, the components of the legs have a length of 1400 – 1600 mm, a width of 900 -1100 mm, and the upper support shaft has a geometric diameter of 57 – 60 mm, length 1500 – 1700 mm thick 2 – 5 mm consists of spur gear timing belt v, moving up to 80Ëš, using a single drive motor. The total electrical energy produced by the single axis solar tracker every 30 minutes is 43.06 Watts and 8 hours of testing (08.00-16.00 WIB) = 750.44 Watts.